Gallery walk sebagai strategi untuk meningkatkan kerjasama dan kreativitas siswa - Yazidah, Nok Izatul; Indrayani, Susi; Rochsun (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to describe the implementation of the Gallery Walk strategy to address deficiencies in geometric conceptual understanding, student cooperation, and creativity in mathematical problem-solving. Design/methodology/approach: A qualitative descriptive Classroom Action Research (CAR) design was conducted over two cycles. The subjects comprised 16 seventh-grade students at a Junior High School in Malang City, focusing on flat-sided 3D shapes. Data were gathered using observation sheets measuring cooperation (discussion participation) and creativity (work quality/originality). Findings: The results indicate that Gallery Walk effectively enhances collaborative dynamics and student ideation. Significant improvements were observed in active participation and analytical skills from Cycle I to Cycle II, validating the effectiveness of this visual exhibition-based method. Practical implications: This research offers a practical alternative for mathematics educators to transition from passive to active learning while simultaneously fostering social and cognitive skills. Originality/value: This study provides empirical evidence on the effectiveness of Gallery Walk specifically within spatial geometry to cultivate 21st-century skills at the junior high school level.   Purpose: Penelitian ini bertujuan mendeskripsikan penerapan strategi Gallery Walk untuk mengatasi rendahnya pemahaman konsep geometri serta rendahnya kerja sama dan kreativitas siswa dalam memecahkan masalah matematika. Design/methodology/approach: Menggunakan desain Penelitian Tindakan Kelas (PTK) deskriptif kualitatif dalam dua siklus. Subjek penelitian melibatkan 16 siswa kelas VII SMP di Kota Malang pada materi bangun ruang sisi datar. Data dikumpulkan melalui lembar observasi yang mengukur indikator kerja sama (partisipasi diskusi) dan kreativitas (kualitas karya/ide). Findings: Hasil menunjukkan bahwa Gallery Walk secara efektif meningkatkan dinamika kolaborasi dan orisinalitas ide siswa. Peningkatan signifikan terlihat pada partisipasi aktif dan kemampuan analisis dari Siklus I ke Siklus II, membuktikan efektivitas metode berbasis pameran visual ini.Practical implications: Memberikan strategi alternatif bagi guru matematika untuk mengubah pembelajaran pasif menjadi aktif, sekaligus mengasah keterampilan sosial dan kognitif siswa dalam lingkungan yang dinamis. Originality/value: Studi ini memberikan bukti empiris mengenai efektivitas Gallery Walk khusus pada materi geometri ruang untuk mengembangkan keterampilan abad ke-21 di tingkat sekolah menengah pertama.